Interaction of filovirus proteins with innate immune pathways - Khan, Hira (fi=Turun yliopisto|en=University of Turku|, 2026)
Ebola virus and Marburg virus are members of the Filoviridae family consisting of negative sense RNA viruses, known for their filamentous virion structure. These viruses have been attributed to cause large-scale, high mortality epidemics, which can cripple public health infrastructure, and lead to transnational issues reminiscent of the COVID19 pandemic. Rapid cellular multiplication, unrestrained inflammation and excessive interference with the antiviral innate immunity are the hallmarks of filoviral infections. The studies in this doctoral thesis have looked at the molecular pathways that VP35 and VP24 proteins of the filoviruses use in antagonising the RIG-I pathway signalling mechanisms and the downstream type I interferon-induced responses. Ebola virus VP35 has been shown to sequester the association of viral double-stranded RNA with PACT, which triggers the activation of RIG-I and phosphorylation of IRF3/IRF7 to induce IFN-α2 production. In addition,VP24 has been shown to bind to importin-α5 inhibiting translocation of interferon-induced, phosphorylated STAT1 to the nucleus and thereby inhibiting the expression of interferon-stimulated genes. New filoviruses have been discovered whose ability to inhibit or delay the innate immune responses is not yet fully understood. Study I in this thesis compares nine filovirus VP24 proteins for their inhibition of RIG-I pathway leading to IFN-β and IFN-λ1 promoter activation and IRF3 phosphorylation. Study II identifies the role of nine filoviral VP24 proteins in inhibiting interferon-induced pathway, while Study III expanded these findings by investigating the role of VP35 proteins of nine filoviruses on both RIG-I and interferon-induced pathway. The results obtained add to the knowledge of the innate immune inhibition capabilities of these viruses and could be utilised in the development of specific antiviral interventions that will assist the innate immune defences to reduce the pathogenicity of filoviruses.